Multilingual Philippine medical thesaurus on diseases pathological conditions, signs and symptoms in Tagalog - Rogacion, Marnelli P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2003)
Medicine is a very complicated subject. We can say that this subject can be understood mostly by the professionals in the said discipline and quite a few number of people coming from other fields. At the same time, the diverse culture and language of the Philippines makes the said subject more complex thus making it even more difficult to understand. This stressed the need for a controlled vocabulary. The researchers believed that a controlled vocabulary specifically in the form of a thesaurus should be made in order to standardize the terminologies used not only by the medical professionals but as well as the medical terms utilized in teaching medical students and most importantly the terms that will be used by doctors when conversing with their patients. It is evident that the existing medical thesauri in the Philippines are largely written in English. Hence, it would be essential to construct a medical thesaurus in Tagalog.
This research attempted to translate Medical Subject Headings (MeSH 2003) Class 23 Diseases - Pathological Conditions, Signs and Symptoms into Tagalog. The objective of this study is to collect and organize information to develop a Multilingual Philippine Medical Thesaurus on Diseases - Pathological Conditions, Signs and Symptoms in Tagalog thus fulfilling the need of the medical field for such thesaurus. In line with this objective the study also aimed to minimize uncertainty with regards to semantic and abstraction of terms.
More than 400 terms were downloaded from the website of MeSH (2003) specifically Class 23, the researcher was able to translate 74 terms to Tagalog through the use of several dictionaries, which were ranked by experts in different field as to its level of authoritativeness and comprehensiveness. The translated terms were validated through interviews with two medical professionals and two non-medical informants. Out of the 74 terms, 52 terms were familiar with the respondents and so the validity of these terms was established. The remaining twenty-two are unfamiliar with the respondents but were still included to serve as a guide for further research. Future researchers in this project should give priority to the translation of the other classes in MeSH (2003) that are believed to be highly important and would be beneficial to its users. This project should also be put into use in order for it to serve its purpose.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Diseases; Filipino language -- Medical Filipino